Application of Human Factors Methods to Ensure Appropriate Infant Identification and Abduction Prevention Within the Hospital Setting. Issue 3 (July 2021) - Webster, Kristen L. W.; Stikes, Reetta; Bunnell, Lisa; Gardner, Amanda; Petruska, Sara
Abstract : Infant misidentification and abduction are recognized as "never" events for hospitals in the United States. As near misses are often unreported, root cause analysis of observed near misses may fail to uncover important contributors. We utilized failure mode and effects analysis to proactively identify and eliminate or reduce the risk of infant misidentification or abduction. We prioritized action plans based upon the highest risk priority failures and developed steps to eliminate the gaps in the infant identification process and the security within the Center for Women & Infants. The analysis identified 28 failure modes. Team discussion of the failure modes also yielded several collateral benefits of improvements in the unit climate. We present and discuss the action plans that were undertaken by the hospital to increase patient safety and reduce the risk of infant misidentification and abduction.